Grad i ljudi u vremenu / Town and People in Time - Bandžović, Safet (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
This text is the review of a book "Life, People and Events - Tuzla between the 19th and 20th century" by Izet Šabotić (Center for Research of Modern and COntemporary History, Tuzla 2019).